Board Independence as a Governance Signal for Corporate Creditworthiness in Indonesian High-Emission Listed Firms - Okevanrianus Putra Hernat; Irwin Irwin; Yanto Yanto; Nunung Apriani; Mis Fertyno Situmeang (Eastasouth Institute, 2026)
This study examines the influence of board independence as a governance signal on corporate creditworthiness among high-issuance listed companies in Indonesia. A quantitative explanatory research design was employed using primary data collected from 150 respondents representing customer perceptions. Data were obtained through a structured questionnaire measured using a five-point Likert scale and analyzed with IBM SPSS Statistics version 25. The analytical procedures included descriptive statistics, validity and reliability testing, normality and heteroscedasticity tests, Pearson correlation, and simple linear regression. The results indicate that all measurement items were valid and reliable, with Cronbach’s Alpha values of 0.912 for board independence and 0.901 for corporate creditworthiness. Board independence had a strong positive correlation with corporate creditworthines. The regression analysis showed that board independence positively and significantly influenced corporate creditworthiness. The coefficient of determination indicated that board independence explained 53.6% of the variation in perceived corporate creditworthiness. These findings support signaling theory and agency theory by demonstrating that independent board oversight signals transparency, accountability, effective risk management, and organizational reliability. The study concludes that strengthening board independence can improve stakeholder confidence and enhance the perceived creditworthiness of high-issuance listed companies in Indonesia.